IFLA '03 Berlin - Filipi Matutinović, Stela (Infotheca - Journal for Digital Humanities, 2024)
Congress, 69th IFLA General Conference and Council which took place in Berlin 1-9 August 2003 was attended by 4,500 participants from 131 countries.